How much Bolshevism is there in America? - Dosch-Fleurot, Arno, 1879-1951; Boon, Hector J. (Salt Lake City, UT : Project Gutenberg, 2024)
"How Much Bolshevism Is There in America?" by Arno Dosch-Fleurot is a collection of investigative articles written in the early 20th century. The work focuses on the author's exploration of the impact of Bolshevism on American society following the Russian Revolution and assesses the potential for similar unrest in the United States. Readers can expect a thorough analysis of social and economic conditions in America as Dosch-Fleurot contrasts it with the turmoil in Europe, particularly in relation to labor movements and class struggles. At the start of the book, the author outlines his journey across the United States to assess how much influence the Bolshevik revolution had on American workers and their socio-economic conditions. He begins by reflecting on America$1 (Bs wealth, contrasting it with the poverty he witnessed in post-war Europe, noting that this prosperity has created a different context for labor unrest. The author raises critical questions regarding the presence of Bolshevism in America and examines various labor movements, particularly the Industrial Workers of the World (I.W.W.), highlighting their distinct nature from Bolshevik ideology. Dosch-Fleurot portrays an America that may experience discontent but lacks the class consciousness apparent in Europe, ultimately suggesting that while there are elements of unrest, serious Bolshevism has not taken root in the American landscape. (This is an automatically generated summary.)s
How much Bolshevism is there in America? by Arno Dosch-Fleurot -- "Russia from the inside," by Hector Boon.
Release date is 2024-05-12
Richard Tonsing, Brian Wilson, Bryan Ness, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Communism -- Soviet Union; Working class -- United States; Labor -- United States; Communism -- United States